Enhanced Energy Storage: Electrochemical Performance of ZnCl2-Activated Carbon Derived from Acacia catechu Bark - Mishra, Pawan; Aryal, Sabin; Oli, Hari; Shrestha, Timila; Mamun, Md Al; Shrestha, Ram Lal Swagat; Bhattarai, Deval (Mongolian Journal of Chemistry, 2024)
In this study, Acacia catechu bark is used for the development of advanced supercapacitor negatrode materials through the synthesis of activated carbon via activation and carbonization at varying temperatures (400, 600, 800 °C) using ZnCl2 as the activating agent. The as-prepared sample is characterized using X-ray diffraction (XRD), Fourier-transform infrared (FTIR) techniques. The specific surface area was evaluated using BET analysis, while 3D morphological assembly of the resulting material was assessed by means of the Field Emission Scanning Electron Microscopy. Cyclic voltammetry, galvanostatic charging and discharging, electrochemical impedance, were conducted to evaluate the material's electrochemical performance. The activated carbon prepared at 800°C (BZAC-8) exhibited a specific capacitance of 259.34 F g-1 at a current density of 1 A g-1 with excellent capacity retention (92.61%) and lower impedance. These findings underscore the potential of utilizing Acacia catechu bark-based active carbon as a negatrode material for advanced energy storing application.